Breaking the Scales: Electrolyte Modeling in Metal-Ion Batteries. (1st January 2017) - Jorn, Ryan; Kumar, Revati
Abstract : Computational modeling is an increasingly important tool for investigating electrolytes at length-scales that are difficult to achieve in the lab. A brief overview of computational studies of electrolytes for metal-ion batteries is presented and the theoretical framework behind these simulations is examined. Particular emphasis is placed on the need for multiscale models that can span orders of magnitude spatially to connect atomistic interactions to large scale properties. These studies range from investigations of the pure electrolyte to interfaces such as those formed by the electrode and electrolyte. Two specific examples are discussed in the context of model development for electrolytes, namely a prototypical carbonate-based electrolyte for lithium ion batteries and a glyme-based material for sodium energy storage.